Persepsi Wisatawan Terhadap Autentisitas Gamplong Studio Alam Sleman Sebagai Daya Tarik Wisata Berbasis Film - Wiwik Sushartami; Mario Albert Arif Hardian (ASEAN Journal on Hospitality and Tourism, 2022)
The purpose of this study is to examine tourists’ perceptions of authenticity at Gamplong Studio Alam Sleman (GSAS) as a film-induced tourism attraction. Theoplacity, a theoretical framework proposed by Belhassen, et al (2008), was adapted as a guide in developing interview questions. The research was conducted using a descriptive-qualitative approach, with six tourists from outside the Province of Daerah Istimewa Yogyakarta (DIY) serving as informants. The findings revealed that the tourists’ perceptions of authentic experience at GSAS as a film-induced tourism attraction are influenced by the interrelationship between tourists’ understandings of the film Bumi Manusia (The Earth of Mankind), the filming set at GSAS as a place component, and the activities carried out by tourists at these tourist attractions. According to the research findings, the experiences of authenticity felt by the informants during a tour at GSAS include riding the Old Train ride as seen in the film, posing like the characters in the film, and re-imagining unique scenes in the film. Authenticity is important in terms of the tourist experience, so tourists’ understanding of the film Bumi Manusia must be compatible with tourist attractions and activities at GSAS.